ChemInform Abstract: Cu‐Catalyzed in situ Generation of Thiol Using Xanthate as a Thiol Surrogate for the One‐Pot Synthesis of Benzothiazoles and Benzothiophenes. Issue 29 (1st July 2013) - Prasad, D. J. C.; Sekar, G.
Abstract: The new title reaction affords a wide range of different substituted benzothiazoles and benzothiophenes in good yields.